Uma Análise de fatores sociodemográficos e sua relação com a escolarização dos filhos em famílias de camadas médias - Dilia Maria Andrade Gloria (2007)
This research, developed in the field of Sociology of Education, with incursions in the Demographic domain, intends to analyze and comprehend the influence of the structure and size of the family, the order of birth and the gender of the children of middle class families in their schooling. Based on reports taken from parents and children of 30 investigated families, it tries to apprehend how these factors affect the specific ways in which each family conceives and acts regarding the school education of their children. Semi-structured interviews and two levels of analyses were done as a central method of investigation: the first level establishes relations between the socio-demographic factors proposed here and the schooling of the children in the investigated families; and a second one in which the focus of the analyses is narrowed so that is put into action the reconstruction of the unique process of schooling of children in three investigated families, highlighting possible details and complexities. The conclusion is that these four socio-demographic factors influence in different ways the schooling of the children, even in the same family. Even though these factors are many times co-related and also vulnerable to a series of other changes, some confirmations are evident: 1) the fact that the parents action is more effective in the families with a nuclear structure because of the presence and bigger involvement of both parents- makes their children, in general, have more benefits in their schooling as opposing to those who live with single parents and rebuilt homes; 2) as to the size of the family, the dilution of the parents resources because of a greater number of children is more evident in material matters than psychological (time and energy), so that the families with three or more children are more affected by the monetary costs of school education and are the ones that do more effort to fulfill their aspiration to a longer and successful schooling; 3) beyond the combining of factors that tend to compete to favor the schooling of the middle or the youngest child, in the majority of cases, the oldest are the ones that present the best school results, and;4) Although in the researched group, the models of socialization are less stereotyped, the separation by sex is felt; on one hand the greater school success of the girls is unquestionable and seems to translate their bigger investment, on the other hand when the choice of the university and the perspectives of the job market